Nitrate Determination of Vegetables in Varzeghan City, North-western Iran - Parviz Nowrouz; Hassan Taghipour; Saeed Dastgiri; Yousef Bafandeh; Kazem Hashemimajd (Tabriz University of Medical Sciences, 2012)
Background: Vegetables play an important role in human nutrition. Nitrate content is a signifi-cant quality criterion to determine characteristic of vegetables. About 80% of nitrate intake in human is from vegetables and fruits. High dietary intake of nitrate is seen as an undesirable be-cause of its association with gastric cancer and infantile methemoglobinemia. Varzeghan, North-western Iran is one of the cities with high Age-standardized incidence rates (ASR) of gastric can-cer in Iran. Currently, in Varzeghan there is no available and accurate information describing ni-trate concentration as one of the important risk factors of vegetables for human consumption.Methods: In this cross sectional study totally 11 types of vegetables (cabbage, lettuce, spinach, parsley, coriander, dill, leek, fenugreek, tarragon, fumitory and mint) from several different green-grocery of Varzeghan were collected in spring (April) and autumn (November and December) 2011 and their nitrate contents were analyzed.Results: Mean nitrate contents at the above noted fresh vegetables were 161, 781, 83, 707, 441,501, 1702, 684, 805, 772 and 191 mg NO3-kg-1 respectively. In none of the 11 fresh vegetablesnitrate content were not more than established limitations.Conclusion: Nitrate concentrations were below of others reported at different countries. The mean concentration of nitrate at all vegetables in autumn was higher than in spring significantly.